The Effect of Financial Literacy and Digital Financial Services on Financial Decision-Making Among Micro and Small Business Owners - Ahmad Fauzan Rahman; Maria Cristina Santos (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Financial literacy and digital financial services have become strategic resources that support the sustainability and competitiveness of micro and small enterprises (MSEs) in the digital economy. Despite the rapid expansion of digital financial ecosystems, empirical findings concerning the interaction between financial literacy and digital financial services in shaping financial decision-making remain inconsistent, particularly among micro and small business owners in developing countries. This study aims to examine the direct and indirect effects of financial literacy and digital financial services on financial decision-making among micro and small business owners. A quantitative explanatory research design was employed using a cross-sectional survey involving 320 micro and small business owners operating in Indonesia. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Financial literacy was measured through financial knowledge, budgeting capability, investment understanding, and risk management. Digital financial services were measured through accessibility, frequency of use, perceived usefulness, and digital transaction intensity. Financial decision-making was evaluated based on financing, investment, savings, and cash flow management decisions. The findings indicate that financial literacy has a significant positive effect on financial decision-making. Digital financial services also exert a significant positive influence while partially mediating the relationship between financial literacy and financial decision-making. Business owners possessing stronger financial knowledge demonstrate greater capability to evaluate financing alternatives, allocate business resources efficiently, and utilize digital financial platforms for operational decisions. The study contributes to the integration of the Theory of Planned Behavior, Technology Acceptance Model, and Resource-Based View by explaining how financial capability and digital technology jointly enhance managerial decision quality. The findings provide practical implications for policymakers, financial institutions, and MSME development agencies in designing integrated financial literacy and digital finance programs that strengthen sustainable business performance.